Information and software for modeling hydrological basins of rivers in the Ukrainian Carpathians - Kolinyk, I. M.; Chaskovskyi, O. H.; Storozhuk, O. L. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
This study addresses the information and software tools used for modeling hydrological basins in the Ukrainian Carpathians, a region distinguished by its complex terrain and diverse ecosystems. The research focuses on a variety of hydrological modeling software, including HEC-HMS, SWAT, and GIS applications, which facilitate the analysis of hydrological processes and the assessment of river runoff dynamics. Furthermore, the integration of meteorological data and land use information is discussed to enhance the accuracy of hydrological models. The results highlight the significance of using advanced software for understanding the impacts of climate change, land use changes, and human activities on water resources in the region. This research aims to provide a framework for sustainable water resource management and contribute to the conservation of aquatic ecosystems in the Ukrainian Carpathians.